Determinan Kualitas Laporan Keuangan Badan Usaha Milik Desa Di Kabupaten Klaten - Wara Novita Ningtyas; Astuning Saharsini (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The purpose of this study was to examine the quality of BUMDesa financial reports in Klaten Regency through the influence of accounting understanding, use of information technology, and training. This research is quantitative and sourced from primary data by distributing questionnaires measured using a likert scale. The population included 391 BUMDesa and the sample was determined using purposive sampling so that 42 BUMDesa were obtained with a total of 84 respondents. The research data was processed through data quality test, classical assumption test, multiple linear regression analysis, as well as hypothesis testing on Statistical Package for Social Sciences (SPSS) software version 25. It was concluded that the quality of BUMDesa financial statements in Klaten Regency was significantly influenced by accounting understanding and the use of information technology, but not significantly influenced by training.